Cheeger-Gromoll type metrics on the (1, 1)-tensor bundles - E. Peyghan; A. Tayebi; L. Nourmohammadifar (Հայաստանի ԳԱԱ)
Using a Riemannian metric on a differentiable manifold, a Cheeger-Gromoll type metric is introduced on the (1, 1)-tensor boundle of the manifold. Then the Levi-Civita connection, Riemannian curvature tensor, Ricci tensor, scalar curvature and sectional curvature of this metric are calculated.
Keywords: Mathematics; Science